ChemInform Abstract: A Ligand‐Free Copper(II)‐Catalyzed Three‐Component Reaction in Poly(ethylene glycol) Medium: A Versatile Protocol for the Preparation of Selected 3‐Indole Derivatives. Issue 8 (1st March 2013) - Chandrasekhar, Srivari; Patro, Vidyavathi; Reddy, Gangireddy Pavan Kumar; Gree, Rene
Abstract The process involves a Knoevenagel condensation followed by Michael addition to give a series of highly functionalized target compounds.